Sweetening Pharmaceutical Radiochemistry by F-18-Fluoroglycosylation: Recent Progress and Future Prospects - Shinde, Sandip S.; Maschauer, Simone; Prante, Olaf (Pharmaceuticals, 2021)
In the field of F-18-chemistry for the development of radiopharmaceuticals for positron emission tomography (PET), various labeling strategies by the use of prosthetic groups have been implemented, including chemoselective F-18-labeling of biomolecules. Among those, chemoselective F-18-fluoroglycosylation methods focus on the sweetening of pharmaceutical radiochemistry by offering a highly valuable tool for the synthesis of F-18-glycoconjugates with suitable in vivo properties for PET imaging studies. A previous review covered the various F-18-fluoroglycosylation methods that were developed and applied as of 2014 (Maschauer and Prante, BioMed. Res. Int. 2014, 214748). This paper is an updated review, providing the recent progress in F-18-fluoroglycosylation reactions and the preclinical application of F-18-glycoconjugates, including small molecules, peptides, and high-molecular-weight proteins.
CRIS-Team WoS Importer:2022-06-17
Keywords: fluorine-18; prosthetic group; 18F-fluoroglycosylation; positron emission tomography; PET